Synthesis and Biological Activities of Some Novel (E)-Alpha-(methoxyimino)benzeneacetate Derivatives with Modified 1, 2, 4-Triazole Moiety. (21st August 2014) - Wang, Xianyou; Wang, Hua; Chen, Peiyun; Pang, Yanping; Zhao, Zhilei; Wu, Guangchen
Abstract : To find new strobilurin analogues with high activity against resistant pathogens, a series of ( E )- α -(methoxyimino)benzeneacetate derivatives containing 1, 2, 4-triazole Schiff base side chain were designed and synthesized. Their structures were confirmed by IR, 1 H NMR, and 13 C NMR, ESI-HRMS, or elemental analyses. Bioassays indicated that most of the target compounds showed moderate to good fungicidal activities against Rhizoctonia solani, Botrytis cinerea Pers., Fusarium graminearum, Cotton rhizoctoniosis, and Blumeria graminis . For example, compounds 6g and 6j exhibited promising antifungal activity against Rhizoctonia solani, Botrytis cinerea Pers., and Fusarium graminearum . Compounds 6c, 6l, and 6m had higher fungicidal activities against Blumeria graminis at the concentration of 50 µ g/mL; inhibitory rate is 91.41%, 92.13%, and 91.77%, respectively.